Effect of grazing, trampling, and fecal deposition on vegetation and soil nutrients, Yukon Kuskokwim Delta Alaska, 2016 ... - Carlson, Lindsay G.; Beard, Karen H.; DeMasters, Thomas; Choi, Ryan T. (NSF Arctic Data Center, 2017)
Herbivores play a key role in the turnover, gains and losses of nutrients in ecosystems. Because nutrients are often limiting, herbivores influence plant growth and chemistry, and their own resource supply. Herbivores typically affect their environment in three ways: they consume aboveground biomass, they trample soil, and they return nutrients to soil via waste materials. The relative importance of these pathways is often unexplored because it requires conducting experiments that isolate these effects. Millions of geese migrate in the spring to sub-arctic coastal wetlands where they play a key role in determining the amount and quality of forage in this habitat. We conducted two field experiments on Carex subspathacea grazing lawns in western Alaska to investigate how these individual processes (grazing, trampling, and fecal addition) influence foliage quality (C:N) and soil nutrients. We isolated goose herbivory effects with five treatments: grazing only, trampling only, fecal addition only, all three ...